2021
DOI: 10.1038/s41598-021-96056-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms linking multi-year La Niña with preceding strong El Niño

Abstract: El Niño-Southern Oscillation (ENSO), characterized by anomalous sea surface temperature in the central-eastern equatorial Pacific, is a dominant interannual variability, impacting worldwide weather and socioeconomics. The ENSO cycle contains irregularity, in which La Niña often persists for more than two years, called “multi-year La Niña”. Observational records show that multi-year La Niña tends to accompany strong El Niño in the preceding year, but their physical linkage remains unclear. Here we show using re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 54 publications
(67 reference statements)
7
35
0
Order By: Relevance
“…Moreover, the PC1 also shows two persistent excess rainfall events: a first event between 1998 and 2000 and a second event between 2010 and 2012, which coincide with the multiyear La Niña events discussed by Iwakiri and Watanabe [18] and Lopes et al [7]. An important feature of these events is that they were immediately preceded by El Niño events-in this case, the 1997-1998 and 2009-2010 periods, respectively, consistent with [18,75,76]. These events are reflected in the rainfall deficits in the SRB presented in Figure 3c.…”
Section: Standardized Precipitation Indexsupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, the PC1 also shows two persistent excess rainfall events: a first event between 1998 and 2000 and a second event between 2010 and 2012, which coincide with the multiyear La Niña events discussed by Iwakiri and Watanabe [18] and Lopes et al [7]. An important feature of these events is that they were immediately preceded by El Niño events-in this case, the 1997-1998 and 2009-2010 periods, respectively, consistent with [18,75,76]. These events are reflected in the rainfall deficits in the SRB presented in Figure 3c.…”
Section: Standardized Precipitation Indexsupporting
confidence: 73%
“…In the last forty years, the El Niño (La Niña) events recorded during 1997-1998 and 2015-2016 (1998-2000 and 2010-2012) stand out as the strongest events, with significant negative consequences for the country [6,9,11,[15][16][17], mainly during La Niña events, which were of longer duration than El Niño events. According to Iwakiri et al [18], this behavior is due to the strong transition asymmetry of ENSO, whereby El Niño concludes quickly, whereas some La Niña events often last more than two years and are defined as multiyear events [7,18,19]. The persistence of multiyear El Niño and La Niña events exacerbate the induced climate impacts, generating persistent floods and droughts worldwide [9,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The mean velocity‐weighted temperature over the Ekman layer, TE, is calculated as follows: TE=vn(z)T(x,y,z), vnez/δsin(zδ+π4), where vn is the normalized velocity weight as a function of the ocean depth z . The Ekman layer depth, δ, is assumed to be constant at 70 m and not sensitive when 50 and 100 m are selected (Figure S3 in Supporting Information , Iwakiri & Watanabe, 2021). The contribution from the GHT is simply defined by the difference between the recharge rate and the EHT.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Indeed, McGregor et al (2013McGregor et al ( , 2014McGregor et al ( , 2016 showed that the Ekman-induced meridional surface transport is an important factor for ENSO phase transition in ocean general circulation model experiments. In addition, Iwakiri and Watanabe (2021) revealed that anomalous Ekman transport is crucial for linking strong El Niño with a subsequent 2-year persistent La Niña.…”
mentioning
confidence: 99%
“…The composite multi-year La Niña is preceded by SSTAs characteristic of a strong El Niño that are absent from the single-year composite La Niña (cf., Figure 1a and Figure S1a in Supporting Information S1). Several previous studies have emphasized this pre-onset strong El Niño condition to explain the generation of multi-year La Niña events (Iwakiri & Watanabe, 2021;Larson & Pegion, 2020).…”
Section: Ssta Characteristics During Single-and Multi-year La Niñasmentioning
confidence: 96%